What we know and what we need to know about developmental and life-course theories. Issue 3 (September 2015) - Piquero, Alex R
This essay considers what is known and what needs to be known about developmental/life-course theories and research. In so doing, it remarks on the period before developmental/life-course came about and then segues into the period of the 1980s in criminological theory where intense and fruitful debates regarding age and crime and criminal careers help to spur developmental/life-course as it is known today. The essay then reviews some prominent developmental/life-course theories, what they tell us about longitudinal offending patterns, and closes with challenges for developmental/life-course theory.